The Technique of Public Order: Evolving Concepts of Criminal Law - Dession, George H. (1955)
T ODAY'S reappraisal of our criminal law was the subject suggested to me asappropriate for the the legal contribution to this university-wide symposium.I agreed, because I think-and hope that as I proceed you may feel-that this isa matter of equal concern to us all. The stimulus to reappraisal derives at leastas much from advances in appreciation of the human creative potential and inknowledge of human personality and behavior, emanating from the arts andsciences, as from audits of the social losses and gains attributable to the operations of enforcement agencies. We have learned that adequate appraisal must take account of the law'simpact on the whole range of community interests; and we know that suchappraisal is not possible without a pooling of the perspectives and skills of all the disciplines represented in a university. The interest we share in this appraisal, and the magnitude of that interest, are implicit in the basic social role of criminal law in all major cultures and through time. One might define this law as the pattern or duster of institutional arrangements on which we rely-short of private retaliation and group warfare-for coping with those deviational acts, personalities and conditions which we consider so destructive of the values we hold as to require drastic intervention in the name of the community as a whole